Agreement between a fitness test and polar s810 for estimating maximum oxygen uptake (2009)
Objective Identifying agreement between data for estimating maximum oxygen uptake obtained by a fitness test and the Polar S810 heart rate monitor. Methods This was an observational agreement study comparing two methods for estimating VO2max (simultaneously and independently). Two protocols were applied to 46 athletes from the Universidad Nacional de Colombia who had been trained in endurance sports (one at rest and maximum effort i). Results Lin's concordance correlation coefficient CCC) was 0.31 (p and lt;0.003). This coefficient did not change substantially when stratified by gender (male: CCC 0.29; 0.04-0.54 95%CI; female CCC 0.15; 0.14-0.45 95%CI), type of sport (group: CCC 0.38; 0.04-0.54 95%CI; individual: CCC 0.16; 0.20-0.52 95%CI) and its value only improved in athletes aged 24.1 to 28 (CCC 0.65; 0.35-0.93 95%CI). Regarding the maximum test, the Polar S810 gave higher or lower values, with 42 mL/kg/min cut-off. Conclusions Agreement between both methods was generally poor and in the different subgroups of athletes; this meant that the results obtained from estimating VO2max could not be exchanged between the fitness and Polar S810 tests.